2016
DOI: 10.1097/icb.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Imaging With Multimodal Adaptive-Optics Optical Coherence Tomography in Multiple Evanescent White Dot Syndrome: The Structure and Functional Relationship

Abstract: Purpose To elucidate the location of pathological changes in Multiple Evanescent White Dot Syndrome (MEWDS) with the use of multimodal adaptive optics (AO) imaging. Methods A five-year observational case study of a 24 year-old year old female with recurrent MEWDS. Full examination included history, Snellen chart visual acuity, pupil assessment, intraocular pressures, slit lamp evaluation, dilated fundoscopic exam, imaging with Fourier-domain optical coherence tomography (FD-OCT), blue-light fundus autofluroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…OCTA is of great importance in revealing that within the corresponding hypofluorescent spots of ICGA, the choriocapillaris and retinal capillary blood flow are completely normal. This reinforces the concept that choriocapillaris may not be involved in this disease and the primary cause of it stands at the level of RPEphotoreceptor complex [1,23,[47][48][49] Acute posterior multifocal placoid pigment epitheliopathy FFA demonstrates early hypofluorescence of the acute posterior multifocal placoid pigment epitheliopathy (APMPPE) lesions and late hyperfluorescence due to staining [50][51][52]. APMPPE has been proposed to be a result of ischemia and acute inflammation of the choriocapillaris, but not of the medium and large sized choroidal vessels, leading to RPE abnormalities [53][54][55].…”
Section: Oct-a In Choroiditis (Choriocapillaropathies and Stromal Chosupporting
confidence: 85%
“…OCTA is of great importance in revealing that within the corresponding hypofluorescent spots of ICGA, the choriocapillaris and retinal capillary blood flow are completely normal. This reinforces the concept that choriocapillaris may not be involved in this disease and the primary cause of it stands at the level of RPEphotoreceptor complex [1,23,[47][48][49] Acute posterior multifocal placoid pigment epitheliopathy FFA demonstrates early hypofluorescence of the acute posterior multifocal placoid pigment epitheliopathy (APMPPE) lesions and late hyperfluorescence due to staining [50][51][52]. APMPPE has been proposed to be a result of ischemia and acute inflammation of the choriocapillaris, but not of the medium and large sized choroidal vessels, leading to RPE abnormalities [53][54][55].…”
Section: Oct-a In Choroiditis (Choriocapillaropathies and Stromal Chosupporting
confidence: 85%
“…The author hypothesized that the initial inflammatory process begins in the inner choroid and then spread to the entire choroid and outer retinal layers [ 13 ]. Conversely, several studies using SD-OCT have demonstrated that MEWDS starts in the outer retina and the photoreceptors, specifically in the EZ [ 17 19 ]. In their MEWDS series, Pichi et al [ 6 ] demonstrated that the choriocapillaris/choroid and superficial and deep retinal capillary networks were comparable to normal healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical signs include deep outer retinal yellow-white lesions that are 100–200 μm in size and foveal granularity. [ 2 ] Fourier-domain optical coherence tomography (OCT) localizes the visually significant changes observed in this disease at the level of the photoreceptors [ Figure 1a ]. These transient retinal changes specifically occur at the level of the inner segment ellipsoid and outer segment/retinal pigment epithelium line.…”
Section: Discussionmentioning
confidence: 99%